The development of wine tourism in the Conegliano Valdobbiadene area - Vasco Boatto; Luigi Galetto; Luigino Barisan; Federica Bianchin (Wine Economics and Policy, 2013)
Tourism has increased significantly in the last decades, in terms of both international visitor flows and revenues. Within these dynamics, assuming the Australian model of wine tourism, which is dominant in many wine-growing areas, the study aims to verify the development stage of Conegliano Valdobbiadene DOCG, one of the most important enological districts in Italy. The paper is divided in three parts. The first introduces the principal changes that have regarded tourist flows in Italy and in Veneto, which is the most important tourist region in the country. The second and third parts describe some of the interpretative models of international (Australia, Argentina, California) and national (e.g. Piedmont, Campania) wine tourism demand in relation to the types that characterize the supply in the case study. In the fourth part, using multivariate analysis methods, the case of Conegliano Valdobbiadene DOCG is investigated by means of a study conducted on a representative sample of 130 wineries. The choice of the model is validated in the case of Conegliano Valdobbiadene DOCG. The results reveal that the area is at a take-off stage, with as yet unrealized development potential. This model could therefore be usefully extended to other wine tourism situations.
Keywords: 330; Conegliano Valdobbiadene - Prosecco; Wine expenditure; Wine tourism type